Recognition of Evamy Et Al P-Zones in the Tertiary Sediments of F- Well, Niger Delta - F.A. Lucas; O.E. Ononeme (Journal of Applied Sciences and Environmental Management)
Palynological evaluation of Tertiary sediments in F- Well, Niger Delta Basin was carried out using Fifty (50) Ditch Cutting samples from a well at different intervals between 2,010ft and 10,170ft. The samples were prepared using standard palynological sample processing technique and analyzed under the microscope. They were about twenty three (23) diagnostic palynomorphs recognized. The evaluation of these  palynomorphs species enabled us to recognize the zones. The presence of diagnostic palynomorphs such as Praedapollis africanus, Peregrinipollis nigericus, Retibrevitricolporites obodoensis and Cicatrisosporites  dorogenesis aided in the establishment of the age and P-zones. The recognized P-zones are P560, P580 and P620 zones. P 560 zone was defined at depth 9,585ft to 9,960ft with increase Retibrevitricolporites oboendensis and the Quantitative Base of Peregrinipollis nigericus P 580 zone was defined at depth 9,585ft to 7,830ft with Quantitative Base of Peregrinipollis nigericus and Top of Cicatrisosporites dorogenesis and P620 zone was defined at depth 7,830ft to 6,690ft with Top Praedapolis africanus and Top Cicatrisosporites dorogenesis. Palynological events and zones gotten from the studied sedimentary succession suggest Oligocene – Early Miocene Age, with numerical value of 32.7 – 22.3 Ma when aligned with the Niger Delta Chronostratigraphic Chart.